Epidemiology of at-risk alcohol use and associated comorbidities of interest among community-dwelling older adults: a protocol for a systematic review - Latanioti, Maria (BMJ Open, 2020)
INTRODUCTION: There is little epidemiological evidence and knowledge about at-risk alcohol use among community-dwelling older adults and their chronic and acute alcohol-related comorbidities of interest. This systematic review will summarise and examine relevant studies about the epidemiology of at-risk alcohol use and associated comorbidities of interest in this population. METHODS: We will search the following databases, without language or date restrictions, from inception to 31 August 2019: Embase.com, Medline Ovid SP, Pubmed (NOT medline[sb]), CINAHL EBSCO, PsycINFO Ovid SP, Central—Cochrane Library Wiley and Web of Science (Core Collection). Search strategies will be developed in collaboration with a librarian. We will use predefined search terms for alcoholism, epidemiology, the elderly, living place and comorbidities of interest, as well as terms related to the identification of “measurements”, “tools” or “instruments” for measuring harm from alcohol use. At-risk status will be determined by the amount of alcohol consumed and any comorbidities of interest associated with at-risk alcohol use, with the latter being documented separately or using an assessment tool for at-risk drinking. We will also examine the bibliographies of all the relevant articles found and search for unpublished studies. We will consider publications in all languages. ETHICS AND DISSEMINATION: No ethical approval is necessary. Results will be presented in national and international conferences on addiction and published in a peer-reviewed journal. PROSPERO REGISTRATION NUMBER: CRD42018099965.